La pédagogie dans le corps ? - Stéphan Mierzejewski; Igor Martinache; Nathalie Jelen; Clément Llena (Éducation et Socialisation)
Physical Education teachers are considered to be a special group in the educational system, as well as a community 'at the forefront' of pedagogy. This article proposes to test these widespread social representations by mobilising quantitative and qualitative data from four collective surveys devoted in whole or in part to PE teachers. By providing a means of comparison with secondary school teachers from a range of disciplines, this data set challenges the characteristics and delineation of the group. It confirms the importance within this disciplinary group of dispositions linked to the pedagogical dimensions of the profession and highlights the different moments of their development during primary socialisation and professional training. In this way, the mechanisms and conditions for the emergence of an effective singular teaching ethos are revealed, without prejudging the effectiveness of the associated teaching practices.